Generalized stability of motion of impulsive Lurie-Postnikov systems with structural perturbation. (1998) - Martynyuk, A. A.; Stavroulakis, I. P.
Abstract : This paper investigates the absolute stability on ℊ s of the zero solution of Lurie-Postnikov systems with impulses and structural perturbation. A number of absolutely stable on ℊ s theorems of the Lyapunov type for Lurie-Postnikov systems are proved, extending and generalizing previous work on the subject. These results are applied to some fourth-order Lurie-Postnikov type systems decomposed into two systems.